Being fashion with a purpose: Exploring consumers' willingness to pay for sustainable fashion - Aleem, A.; Loureiro, S. M. C.; Santos M. (Global Fashion Management Conference Proceeding, 2024)
Our daily lives are significantly influenced by the fashion industry, which shapes our identities and reflects our social and cultural values. However, the conventional fashion sector has been linked to numerous social and environmental problems, raising concerns about its sustainability. The detrimental environmental effects of fast fashion have increased the demand for other strategies that promote sustainability without sacrificing style and customer preferences. As a result, sustainable fashion has become a promising response to these problems. This research analyses consumers' willingness to pay for sustainable fashion, acknowledging the important role of brand coolness and sustainability perception in influencing consumers' decisions. Study findings demonstrate a shift toward more responsible consumption patterns within the fashion sector, which can lead to a more responsible future where fashion and sustainability coexist.